ENTREPRENEURIAL SKILLS OF ENTREPRENEURS AND ENTREPRENEURSHIP DEVELOPMENT IN NIGERIA - Ogechukwu Chrysantus Udegbulem (Knowledgeable Research A Multidisciplinary Journal, 2025)
The study assessed skills and entrepreneurship. Entrepreneurs are skilled individuals who create, innovate, recognize and take calculated risk in an attempt to solve their entrepreneurial challenges.  Entrepreneurial skills are requisite hard, soft, transferable, personal and knowledge-based skills used for the execution of entrepreneurial activities in a sustainable manner for rapid socio-economic growth, development and high productivity. Examples of this entrepreneurial skills include business management skills, teamwork and leadership skills, communication skills, customer - service skills, financial skills, analytical and problem-solving skills, time management and organizational skills, strategic thinking and planning skills, sales skills, stress management skills, social influence and self-motivation. The study reviewed the concepts of entrepreneurship, entrepreneur, skills and entrepreneurial skills. The challenges confronting the entrepreneur were also discussed and possible solutions were made. The study suggested that entrepreneurs should utilize social media and AI models to connect with the target audiences; entrepreneurs should constantly identify the latest news and achievements in the market and update their knowledge. Also, streamlining and harmonizing regulatory framework, mainstreaming risk mitigation instruments among others were suggested.